The Influences of Changes in Physical Activity Levels With Easing Restriction of Access to the University Campus on Empathy and Social Supports in College Students During the COVID-19 Pandemic. (May 2022) - Shima, Takeru; Nakao, Hayato; Tai, Kentaro; Shimofure, Tomonori; Jesmin, Subrina; Arai, Yoshihiro; Kiyama, Keiko; Onizawa, Yoko
College students in Japan are restricted from accessing the campus associated with promoting online classes during the COVID-19 pandemic; it would lead to less physical activity and poor relationships with others. Here, we measured 887 college students' amounts of physical activity, sitting time, self-reported cognitive and affective empathy, and perceived social support before and after easing campus entrance restrictions. The amounts of total activity, vigorous-intensity, and moderate-intensity activity in college students, both male and female, increased after easing restrictions of accessing the campus compared during restrictions. The amounts of walking activity were unchanged. Self-reported cognitive empathy scores significantly increased in female students after mitigating restrictions, but not in males. Furthermore, the total of physical activity's change amounts was positively correlated with changes in the scores of affective empathy and perceived family support. In addition, changes in the scores of affective empathy were positively correlated with perceived social help from family, friends, and close people. The current findings imply that increasing physical activity levels after easing restriction of access to the campus would lead to a better quality of life in young adults during the COVID-19 pandemic.